Open source control device for industry 4.0 based on RAMI 4.0 - Melo, Pablo F. S. [UNESP]; Godoy, Eduardo P. [UNESP]; Ferrari, Paolo; Sisinni, Emiliano (MDPI, 2021)
The technical innovation of the fourth industrial revolution (Industry 4.0—I4.0) is based on the following respective conditions: horizontal and vertical integration of manufacturing systems, decentralization of computing resources and continuous digital engineering throughout the product life cycle. The reference architecture model for Industry 4.0 (RAMI 4.0) is a common model for systematizing, structuring and mapping the complex relationships and functionalities required in I4.0 applications. Despite its adoption in I4.0 projects, RAMI 4.0 is an abstract model, not an implementation guide, which hinders its current adoption and full deployment. As a result, many papers have recently studied the interactions required among the elements distributed along the three axes of RAMI 4.0 to develop a solution compatible with the model. This paper investigates RAMI 4.0 and describes our proposal for the development of an open‐source control device for I4.0 applications. The control device is one of the elements in the hierarchy‐level axis of RAMI 4.0. Its main contribution is the integration of open‐source solutions of hardware, software, communication and programming, covering the relationships among three layers of RAMI 4.0 (assets, integration and communication). The implementation of a proof of concept of the control device is discussed. Experiments in an I4.0 scenario were used to validate the operation of the control device and demonstrated its effectiveness and robustness without interruption, failure or communication problems during the experiments.
Keywords: Control device; Industry 4.0; OPC UA; Open‐source; RAMI 4.0; Raspberry Pi